(untitled) (Sudurpaschim Spectrum, 2024)
The major objective of the study is to examine the impact of market risk on cross-section of expected stock returns from Nepali capital market. In doing so, stock beta is considered as the proxy of market risk. The research design adopted in this study consists of descriptive and casual comparative research design to ascertain and understand the directions, magnitudes, and forms of observed relationship between the dependent and independent variables by using the data set of 576 observations for the period of 2010/11 to 2021/22 from the 48 sample firms. Furthermore, this study has applied different statistical as well as econometrics tools such as portfolio analysis, descriptive statistics, correlation matrix, and multiple regression analysis. The findings reveal that market risk has the significant positive impact on cross-section of common stock returns in Nepali capital market.